PEMIKIRAN TEORI HUKUM ISLAM IMAM AL-JUWAYNĪ Analisis Pemikiran Uṣūl Fiqh Imam al-Juwaynī, Serta Posisinya Dalam Ijtihād - Chamim Thohari (Fakultas Syariah (Syari'ah Faculty ), 2016)
Abstract This research discuss about the Uṣūl al-Fiqh (the sources of jurisprudence) and fiqh (jurisprudence) in al-Juwaynī’s thought, and his contribution for development of Islamic law. The methodology which is used in this research is a library research with content analysis to describe the unique sides of al-Juwaynī’s thoughts. The result of this research is, that al-Juwaynī was a Shāfi‘īte, but he diverted in many issues from al-Shāfi‘ī. He was one of the main scholars of his time to concentrate on Ushūl al-Fiqh as a science and as the basis of fiqh. Before him, scholars of Uṣūl al-Fiqh seem to have taken one of two opposite opinions. However al-Juwaynī argued that the truth was somewhere in between. Al-Juwaynī ’s contribution in Uṣūl al-Fiqh is his use of middle ground solutions. In fiqh, al-Juwaynī was independent to a great extent. It seems that only truth mattered to him, despite his recognition that he belonged to the Shāfi‘ī school of fiqh.